American foreign policy: Alliance politics in a century of war, 1914-2014 - James W. Peterson (Bloomsbury, 2014)
The text aims to uncover the roots of the United States' near perpetual involvement in war since the beginning of WWI in 1914. Using alliance politics as the main framework of analysis, it offers a new interpretation that contrasts with the traditional views that war is an interruption of the American foreign policy emphasis on diplomacy. Instead, it posits that war has been the norm during the past century while peaceful interludes were but a time of respite and preparation for the next conflict.